Analysis and reading of the quality of an urban public space via space syntax - Femmam, Nadia; Boukhabla, Moufida; Mazouz, Said; Femmam, Asma (Technium Social Sciences Journal, 2023)
Biskra is one of the Algerian cities that has undergone a very accelerated evolution through the different periods of its history. It is confronted with serious problems related to various dysfunctions in particular in its planned urban structure and in its social structure suffering from several social ills, whether in: housing spaces, equipment or urban public spaces. The latter present many anomalies depending on the consumption of space, identification, orientation and behavior. The objective of this work seeks to read and analyze the quality of permeability and legibility in urban public spaces in the neighborhood of El-Alia northeast Biskra, how the space affects the movement of pedestrians and therefore their behavior and to make a comparison between what exists in reality and what is proposed in the development plan of the neighborhood of El Alia northeast by the Office of Studies and Achievements in Town Planning URBA in terms of these two concepts, in order to affirm or deny whether the design of the spatial structure proposed by the URBA has remedied the various deficiencies and anomalies in the existing. We proposed as a model of analysis and reading the combination of two methods obtained from the literature, namely the method of responsive environments and the method of space syntax.